Axial Length Changes Following Surgical Intervention in Children With Primary Congenital Glaucoma - Al Dalgan, Hind A.; Al Obaida, Ibrahim A.; Al Owaifeer, Adi M.; Ahmad, Khabir; Malik, Rizwan (Frontiers in Ophthalmology, 2021)
Background Primary congenital glaucoma (PCG) is a challenging condition to diagnose, treat and effectively monitor. Serial assessment of intraocular pressure (IOP), optic disc cupping, refraction, and axial length (AxL) after surgery are useful to assess disease control. This study aimed to evaluate AxL changes in relation to IOP changes following glaucoma surgery in children with PCG. Methods We retrospectively studied AxL changes in children with PCG undergoing surgery. Eyes of children aged ≤ 4 years that did not have prior ocular surgery and that underwent at least one glaucoma surgery during the course of follow-up at the King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia, between June 2014 and July 2018, were included. The effect of change in IOP on change in AxL was estimated using linear mixed effects models. Results A total of 105 eyes (of 72 children) with PCG underwent glaucoma surgery representing 26.4% (105/397) eyes. The mean ± SD age of children at baseline was 3.53± 4.04 months. At baseline, the mean IOP and AxL were 26.63 ± 9.57 mmHg and 21.67 ± 1.82 mm, respectively. During the course of follow-up post-surgery, the IOP decreased by a mean of 7.25 ± 12.08 mmHg while the AxL increased by a mean of 0.70± 1.40 mm. A multivariable mixed effects linear regression revealed that change in AxL was significantly associated with change in IOP (p=0.030) and time since first surgery (p<0.001). A substantial reduction in IOP (≥35 mmHg) was needed at 3 months post-surgery, for AxL to regress. Conclusion In children with PCG who undergo glaucoma surgery, change in IOP significantly influences change in AxL. For AxL to regress, a more substantial reduction in IOP is needed post-surgery.